(3QSGdI aj Yde GdWHjYIs - (3fhQ GdOjf Ydj GdCfOdSjs
(3ChdgG (B:s
(3bGd GdGeGe GdGfOdSi QMeg Gdgd JYGdi ai cJGH cfR GdYdhe hGdOQ GdefXhe Cf CaVd GdYdhe Yde eYQaI Gddg YR hLd s
(3BNQgG (B:s
(3hai gPG GdbjGS CcHQ Odjd hChVM HQgGf Ydi gPg GdUfYI GdTQjaI hMLI Ydi ef GacQ hGdUMM eG PcQfGg fe GdSO GdHOjY hGdeYfi GdQajY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(255) s
Keywords: (3GdcjejGA h GdWHjYjGJs